Dr. Artem Ayvazyan — Deep Plane Facelift — Porto Alegre - Ayvazyan, Artem (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Artem Ayvazyan, practicing in Porto Alegre, Brazil. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003174; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; brazil; porto alegre